Análisis del aporte del POCUS a la población atendida en la consulta de medicina familiar y comunitaria, en el Área de Salud de Talamanca, en el primer semestre del 2019 - Simpson Johnson, Teyshell M. (2020)
Objective: To analyze the contribution of the POCUS to the population attended in the consultation of family and community medicine, in the Health Area of Talamanca, in the first half of 2019. Methodology: Quantitative observational descriptive and retrospective study. The age, gender, reference health center, district, date of care, reason for reference, ultrasonographic findings and the final status of 196 patients registered in the database are analyzed. Results: In the family and community medicine service, the patients with age range between 51 - 60 years, were the ones that added the highest number of assessments, representing 16.76%. However, by grouping all adults over 60 years of age served, they accounted for more than one third of the population served. The female gender accounted for 54.6% of the patients and the center where the largest number of patients were referred to, was the EBAIS Bribrí (64.9%), however, the majority live in the Sixaola district of Talamanca (34.6%). The reasons for reference were due, for the most part, to prostate, renal and urinary tract pathologies (30.8%). This correlated with the ultrasonographic findings, since the prostate, renal and urinary tract pathology was the one that represented the first place in pathological findings (27,74%), followed by the pathology of the gastrointestinal and abdominal system in 24,38%, and thirdly, osteomuscular and soft tissue pathology in 15,96%. The POCUS confirms the diagnosis in 15.7%, guides the diagnosis in 32.4%, changes the diagnosis in 7% and discards pathological findings in 44.3%. In this study, it was determined that only 9.4% of patients were referred to another level of care, of which 5 patients have already been treated in the subspecialties and the diagnostic correlation with the family doctor has been 100%. In addition, 38.7% of patients are discharged, while 51.9% are followed up in family medicine. In the interviews that were conducted, it is reported that the waiting list of the family medicine service, to be assessed and even apply the POCUS as a diagnostic tool, is 6 - 8 weeks, while the waiting list of the Radiology service of the HTFL is 12 months. Conclusions: POCUS has been a valuable tool in a rural area such as the Talamanca Health Area; it has increased the resolving capacity of the family medicine service, it does not contribute to the increase of HTFL waiting lists, it facilitates the access of lagged populations to health services and special studies, the waiting time for specialized assessment decreases compared to the HTFL, allows the prioritization of patients making appropriate references and directed to the specialties.